2018
DOI: 10.1016/j.pedneo.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy in a very young infant with mitral valvuloplasty

Abstract: The youngest case of post-operative TMA underscores the critical coagulopathy after the first surgical intervention for congenital heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Only one patient suffered a clinical relapse and the authors reported that in addition to cardiac bypass surgery, another potential nidus for developing TMA was recent history of ABO incompatible red blood cell transfusion . Of the two patients requiring other therapy in addition to TPE, one patient who developed TMA after mitral valvuloplasty, underwent repeat valvuloplasty with improvement in TMA symptoms . Another patient who developed TMA after myomectomy received eculizumab and demonstrated a complete response …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only one patient suffered a clinical relapse and the authors reported that in addition to cardiac bypass surgery, another potential nidus for developing TMA was recent history of ABO incompatible red blood cell transfusion . Of the two patients requiring other therapy in addition to TPE, one patient who developed TMA after mitral valvuloplasty, underwent repeat valvuloplasty with improvement in TMA symptoms . Another patient who developed TMA after myomectomy received eculizumab and demonstrated a complete response …”
Section: Resultsmentioning
confidence: 99%
“…15 Of the two patients requiring other therapy in addition to TPE, one patient who developed TMA after mitral valvuloplasty, underwent repeat valvuloplasty with improvement in TMA symptoms. 28 Another patient who developed TMA after myomectomy received eculizumab and demonstrated a complete response. 35 Outcomes of the five patients not receiving TMA directed treatment included death in three patients and it was reported that these patients had a delay in diagnosis of TMA.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Device-related TMA as a secondary TMA could be difficult to diagnose if device implementation was performed years ago. Previous reports have demonstrated that cardiac valve-related TMA can appear soon after cardiac valve surgery [4,5], where it was diagnosed by excluding other TMA possibilities [6]. Here, we report the case of an older woman with a chief complaint of dyspnea and the pathophysiology of secondary TMA.…”
Section: Introductionmentioning
confidence: 85%
“…(1) progressive anemia; (2) no history of hemolysis before mitral repair; (3) soy urine after operation; (4) residual mitral regurgitation found by echocardiography. Transthoracic echocardiography and transesophageal echocardiography are important for the diagnosis of mechanical hemolysis after mitral repair [Aoyagi 2007;El Sabbagh 2018;Tsang 2019;Matsunaga 2018].…”
Section: E168mentioning
confidence: 99%